Alternative perspectives of safety in home delivered health care: a sequential exploratory mixed method study. (20th May 2016) - Jones, Sarahjane
Abstract: Aim: The aim of this study was to discover and describe how patients, carers and case management nurses define safety and compare it to the traditional risk reduction and harm avoidance definition of safety. Background: Care services are increasingly being delivered in the home for patients with complex long‐term conditions. However, the concept of safety remains largely unexplored. Deign: A sequential, exploratory mixed method design. Methods: A qualitative case study of the UK National Health Service case management programme in the English UK National Health Service was deployed during 2012. Thirteen interviews were conducted with patients ( n = 9) and carers ( n = 6) and three focus groups with nurses ( n = 17) from three community care providers. The qualitative element explored the definition of safety. Data were subjected to framework analysis and themes were identified by participant group. Sequentially, a cross‐sectional survey was conducted during 2013 in a fourth community care provider (patient n = 35, carer n = 19, nurse n = 26) as a form of triangulation. Findings: Patients and carers describe safety differently to case management nurses, choosing to focus on meeting needs. They use more positive language and recognize the role they have in safety in home‐delivered health care. In comparison, case management nurses described safety similarly to the definitions found in the literature. However, when offered the patient and carer definition of safety, they preferentially selected this definition to their own or the literature definition. Conclusion: Patients and carers offer an alternative perspective on patient safety in home‐delivered health care that identifies their role in ensuring safety and is more closely aligned with the empowerment philosophy of case management.